Small-particle-size spheroidic alumina product and preparation method thereof
Through the primary calcination process, the particle size and calcining conditions of the alumina raw material are controlled to form spherical alumina products with high α-phase content and low impurities, which solves the problem of insufficient thermal conductivity of existing alumina fillers and achieves higher thermal conductivity and lower production costs.
Patent Information
- Application Number
- CN202510008860.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-07
AI Technical Summary
The existing alumina fillers have shortcomings in thermal conductivity, and the preparation process is complex, and the product has high impurity content, which cannot meet the needs of high thermal conductivity applications.
By using the primary calcination method, small crystal nuclei of micro-nano-level are formed by controlling the particle size, calcining temperature and calcining time of aluminum-containing raw materials, and small-particle spherical alumina products with a particle size of 0.1~10μm, an α-phase content of more than 95%, and a low impurity element content.
It has achieved regular morphology, improved thermal conductivity and reduced impurity element content of small-particle spherical alumina products. It is suitable for high thermal conductivity applications, with simple process and low production costs.
Smart Images

Figure CN119569092A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alumina materials, and in particular relates to a small-particle-size quasi-spherical alumina product and a preparation method thereof. Background Art
[0002] With the rapid development of the electronics industry, people have higher and higher requirements on material properties, especially thermal conductivity. Alumina, as an important thermal conductive filler, is widely used in various fields, such as electronics, aviation, and automobiles. Usually, ordinary calcined alumina is difficult to add in large quantities to thermal conductive fillers due to its irregular morphology, resulting in the failure to improve thermal conductivity and unable to meet high thermal conductivity applications.
[0003] Spherical alumina, as a spherical powder, solves the problem of large-scale filling, but due to the processing technology of spherical alumina, it is difficult to convert the alumina phase itself into α-phase alumina. In addition, a spherical alumina microsphere is usually composed of multiple alumina grains, which also increases the interface and thermal resistance, and cannot meet the needs of higher thermal conductivity.
[0004] The existing processes for preparing quasi-spherical alumina, such as the preparation method and quasi-spherical alumina products disclosed in patent CN118026228A, can obtain alumina with a relatively regular morphology and a high α-phase content, but there are problems such as complex preparation process and high impurity content of the product. Moreover, when used as a thermally conductive filler, there is still a need to improve its thermal conductivity.
[0005] Therefore, we further developed an alumina filler with a simple preparation process, more regular morphology and better thermal conductivity. Summary of the invention
[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides a small-particle quasi-spherical alumina product and a preparation method thereof. Without adding additives, a one-time calcination method is adopted. By controlling the particle size, calcination temperature and calcination holding time of the raw materials, the aluminum-containing raw materials are allowed to develop into micro-nano-level small crystal nuclei in one step, and grow to obtain a small-particle quasi-spherical alumina product with a particle size of 0.1~10μm, an α-phase content of more than 95%, a low impurity element content and a regular morphology.
[0007] The technical solutions adopted in the present invention are:
[0008] A method for preparing a small-size spherical alumina product comprises the following steps:
[0009] S1, placing aluminum-containing raw materials with a particle size of 0.1-1 μm in a kiln for calcination at a temperature of 1000-1200°C and a calcination holding time of 5-10 hours;
[0010] S2, washing, drying, crushing and classifying the calcined product of step S1 to obtain a small-size spherical alumina product.
[0011] Furthermore, in step S1, the aluminum-containing raw material is one or more of industrial alumina, industrial aluminum hydroxide, and boehmite.
[0012] Furthermore, the particle size of the aluminum-containing raw material is 0.1-0.8 μm, or the particle size of the aluminum-containing raw material is 0.1-0.5 μm.
[0013] Furthermore, in step S1, the calcination temperature is 1050-1100°C, and the calcination holding time is 5-6 hours.
[0014] Further, in step S2, cleaning and drying are performed, which specifically includes:
[0015] Add the calcined product into a reaction kettle or a stirring tank, and stir and mix thoroughly with preheated pure water;
[0016] Then, ion exchange resin is added to carry out a hydrothermal stirring reaction;
[0017] After the hydrothermal stirring reaction, the ion exchange resin is removed, and the slurry is filtered or suction filtered and dried.
[0018] Furthermore, one or more of the following conditions are included:
[0019] The pure water is pure water with a conductivity of less than 5 μs / cm;
[0020] The calcined product is stirred and mixed with preheated pure water, and the pH is adjusted to 6.5-7.5;
[0021] The amount of pure water added is 1.5 to 2 times the mass of the aluminum-containing raw material;
[0022] The temperature of the hydrothermal stirring reaction is 50-80°C, and the reaction time is 2-3h;
[0023] The ion exchange resin is one or more of benzenesulfonic acid, ammonium benzenesulfonate, and methyl lactate;
[0024] The added amount of the ion exchange resin is 0.1-0.2% of the mass of the aluminum-containing raw material.
[0025] Furthermore, the ion exchange resin is loaded into a filter bag or a porous container and then put into a reaction kettle or a stirring tank to undergo a hydrothermal stirring reaction with the calcined product. After the hydrothermal stirring reaction, the filter bag or porous container containing the ion exchange resin is taken out to obtain the slurry.
[0026] Further, in step S1, the kiln is one of a push plate kiln, a tunnel kiln, and a shuttle kiln;
[0027] And / or, in step S2, the dried product is crushed by a ball mill and / or a jet mill, and the crushing time is 5 to 6 hours.
[0028] A small-particle quasi-spherical alumina product has a particle size of 0.1-10 μm, an aspect ratio of 0.8-1.4:1, an α-phase content of more than 95%, and a total impurity element content of less than 200 ppm.
[0029] Furthermore, the small-particle quasi-spherical alumina product has a particle size of 0.2-0.8 μm.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The method for preparing a small-particle spherical alumina product of the present invention adopts a one-time calcination method without adding an auxiliary agent, by controlling the particle size of the aluminum-containing raw material to 0.1-1 μm (preferably 0.1-0.5 μm), the calcination temperature to 1000-1200°C and the calcination time to 5-10 hours, so that the aluminum-containing raw material is allowed to develop into micro-nano-level small crystal nuclei in one step, and grow to obtain a small-particle quasi-spherical alumina product with small particle size, high α-phase content, low impurity element content and regular morphology.
[0032] 2. The preparation method of the present invention does not add additives, which reduces the introduction of ions and impurity elements, and is conducive to obtaining products with higher density and greater hardness; and after calcination, the calcined product is reacted and cleaned with an ion exchange resin, so that the obtained small-particle spherical alumina product has a lower content of impurity elements and has better thermal conductivity when used as a thermal conductive filler.
[0033] 3. In the preparation of traditional alumina filler products, after adding additives, a relatively lower calcination temperature can be used to achieve the development of crystal nuclei and the growth of grains, and obtain particles of uniform size (on the contrary, when calcination is performed without adding additives, a higher calcination temperature is required to achieve the development of crystal nuclei and the growth of grains, etc.); however, the preparation method of the present invention finds that by using raw materials with a particle size of 0.1~1μm, without adding additives, using a relatively lower calcination temperature (1000~1200℃), calcining and heat preservation for 5~10h, a product with regular morphology can be obtained by calcining once, and the product has a small particle size, a high α phase content, a low impurity element content, and a spherical structure, which can better meet the needs of high thermal conductivity applications.
[0034] 4. The preparation method of the present invention has a simple process, does not require the addition of additives, and has a low calcination temperature, which makes the production cost low, is suitable for promotion and application, and has better economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 This is a SEM image of the small-particle spherical alumina product obtained in Example 1 of the present invention.
[0037] Figure 2 This is a SEM image of a small-particle spherical alumina product obtained in Example 2 of the present invention.
[0038] Figure 3 This is a SEM image of a small-particle quasi-spherical alumina product obtained in Example 3 of the present invention.
[0039] Figure 4 This is the SEM image of the alumina product obtained in Comparative Example 1.
[0040] Figure 5 This is the XRD diagram of the small-particle spherical alumina product obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0041] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present invention. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.
[0042] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0043] The present embodiment provides a method for preparing a small-size spherical aluminum oxide product, comprising the following steps:
[0044] S1, select aluminum-containing raw materials with a particle size of 0.1~1μm, put the aluminum-containing raw materials into a sagger, and then place it in a kiln for calcination, or directly place the aluminum-containing raw materials in the kiln for calcination; control the calcination temperature within the range of 1000~1200℃, and control the calcination insulation time to be 5~10h.
[0045] The aluminum-containing raw material is a combination of one or more of industrial alumina, industrial aluminum hydroxide and boehmite.
[0046] The particle size of the aluminum-containing raw material is preferably controlled within the range of 0.1 to 0.8 μm, and more preferably within the range of 0.1 to 0.5 μm.
[0047] The calcination temperature can be more optimally controlled within the range of 1050-1100°C, with a calcination holding time of 5-6 hours.
[0048] The kiln used for calcination is one of push-plate kiln, tunnel kiln and shuttle kiln.
[0049] By controlling the particle size of aluminum-containing raw materials, the calcination temperature and the calcination and insulation time, the development of micro-nano-level tiny crystal nuclei and the growth of grains can be completed in a single calcination process without adding additives.
[0050] S2, washing and drying the calcined product obtained in step S1, and crushing and classifying the dried product to obtain a small-size spherical alumina product.
[0051] Preferably, in step S2, cleaning and drying are performed, which specifically includes:
[0052] The calcined product is added to a reactor or a stirring tank, and is fully stirred and mixed with preheated pure water to fully disperse the calcined product. Then, an ion exchange resin is added to the fully mixed liquid, the temperature is maintained, and the stirring is continued to perform a hydrothermal reaction. After the hydrothermal reaction is completed, the ion exchange resin is removed, the slurry after the reaction is filtered or filtered, the filtrate or filtrate is removed, and the filter material is dried. The purpose is to further remove impurity elements in the calcined product through cleaning and ion exchange.
[0053] Further preferably, pure water with a conductivity of less than 5 μs / cm is used, and the amount (mass) of pure water added is controlled to be 1.5 to 2 times the mass of the initial aluminum-containing raw material; after preheating to 50 to 80°C in a reactor or a stirring tank, the calcined product is added and stirred and mixed, and the pH is adjusted to 6.5 to 7.5 (i.e., 7.0±0.5), preferably adjusted to 7.0.
[0054] Then, add ion exchange resin to the above reactor or stirring tank, keep the temperature at 50-80°C, continue stirring and reacting for 2-3 hours, perform ion exchange, and replace the impurity ions in the calcined product. The ion exchange resin is one or more of benzenesulfonic acid, ammonium benzenesulfonate, and methyl lactate; preferably, the addition amount (mass) of the ion exchange resin is 0.1-0.2% of the mass of the initial aluminum-containing raw material.
[0055] The use of ion exchange resin for cleaning can, on the one hand, reduce the content of impurity ions in the alumina product, and on the other hand, reduce the viscosity of the alumina product in subsequent applications and improve its thermal conductivity.
[0056] Preferably, the ion exchange resin is placed in a filter bag or a porous container, and then placed in a reactor or a stirring tank for hydrothermal stirring reaction with the calcined product. After the hydrothermal stirring reaction for 2 to 3 hours, the filter bag or porous container containing the ion exchange resin is taken out to obtain the slurry after ion exchange. The particle size of the ion exchange resin needs to be controlled to be larger than the pore size of the filter bag or the porous container to prevent the ion exchange resin from entering the slurry.
[0057] The ion exchange resin is placed in a filter bag or a porous container for ion exchange reaction, and can be directly taken out after the treatment is completed. The separation operation is more convenient and can avoid the residue problem caused by direct mixing of the ion exchange resin with the material, ensuring a higher purity product.
[0058] The cleaned and dried filter material is crushed by a ball mill and / or a jet mill. The ball mill or jet mill is used for crushing for 5 to 6 hours to obtain a small-size spherical alumina product.
[0059] The following is a more specific example.
[0060] Example 1
[0061] Industrial alumina with a particle size of 0.5 μm is used as the aluminum-containing raw material. 1 kg of the industrial alumina is put into a sagger and calcined in a tunnel kiln at a calcination temperature of 1050° C. and a calcination holding time of 5 hours.
[0062] Take 2 kg of pure water with a conductivity of less than or equal to 5 μs / cm, and preheat it to 70°C in a reactor; add the calcined product to the reactor, stir and mix with pure water, and adjust the pH to about 7.0; then add a filter bag containing 20 g of methyl lactate to the reactor, keep warm and stir to perform ion exchange, and take out the filter bag containing methyl lactate after 2 hours of ion exchange reaction; filter the treated slurry by suction, and dry the filter material. The dried filter material is ground and crushed in a ball mill at a speed of 500 rad / min for 6 hours; after grinding, it is classified to obtain a small-sized spherical alumina product.
[0063] Example 2
[0064] Industrial alumina with a particle size of 0.6 μm is used as the aluminum-containing raw material. 1 kg of the industrial alumina is put into a sagger and calcined in a tunnel kiln at a calcination temperature of 1070°C and a calcination holding time of 5.5 hours.
[0065] Take 2 kg of pure water with a conductivity of less than or equal to 5 μs / cm, and preheat it to 75°C in a reactor; add the calcined product to the reactor, stir and mix with pure water, and adjust the pH to about 7.0; then add a filter bag containing 15 g of benzenesulfonic acid to the reactor, keep warm and stir to perform ion exchange, and take out the filter bag containing benzenesulfonic acid after 2.5 hours of ion exchange reaction; filter the treated slurry and dry the filter material. The dried filter material is ground and crushed in a ball mill at a speed of 500 rad / min for 6 hours; after grinding, it is classified to obtain a small-sized spherical alumina product.
[0066] Example 3
[0067] Boehmite with a particle size of 0.5 μm is used as the aluminum-containing raw material. 1 kg of the boehmite is put into a sagger and calcined in a tunnel kiln at a calcination temperature of 1090° C. and a calcination holding time of 5 hours.
[0068] Take 1.5 kg of pure water with a conductivity of less than or equal to 5 μs / cm, and preheat it to 60°C in a reactor; add the calcined product to the reactor, stir and mix with pure water, and adjust the pH to about 7.0; then add a filter bag containing 10 g of ammonium benzenesulfonate to the reactor, keep warm and stir to perform ion exchange, and take out the filter bag containing ammonium benzenesulfonate after 2 hours of ion exchange reaction; filter the treated slurry by suction, and dry the filter material. The dried filter material is ground and crushed in a ball mill at a speed of 500 rad / min for 6 hours; after grinding, it is classified to obtain a small-sized spherical alumina product.
[0069] Comparative Example 1
[0070] Industrial alumina with a particle size of 0.5 μm is used as the aluminum-containing raw material. 1 kg of the industrial alumina is mixed with 1 g of an additive, and then put into a sagger, which is then placed in a tunnel kiln for calcination at a temperature of 1050°C and a calcination holding time of 5 hours.
[0071] Take 2 kg of pure water with a conductivity of less than or equal to 5 μs / cm, and preheat it to 70°C in a reactor; add the calcined product to the reactor, stir and mix with pure water, and adjust the pH to about 7.0; keep warm and stir for cleaning, filter the slurry after cleaning for 2 hours, and dry the filter material. The dried filter material is ground and crushed in a ball mill at a speed of 500 rad / min for 6 hours; after grinding, it is classified to obtain a spherical alumina product.
[0072] The microscopic morphology of the alumina products of Examples 1 to 3 and Comparative Example 1 was observed using a scanning electron microscope. The observation results are as follows: Figures 1 to 4 The alumina products obtained in Examples 1 to 3 have a relatively rounded surface, a spherical structure, a uniform particle size distribution, and a very regular morphology. Figures 1 to 3In comparison, the surface of the aluminum oxide product prepared in Comparative Example 1 is relatively round, but the particle size distribution uniformity is poor, the morphology regularity is biased, and most of them are elliptical; analysis shows that after adding additives and calcining at 1050°C, the aluminum oxide grains will develop to a certain extent in an elliptical shape, which is not conducive to the formation of a spherical structure, see Figure 4 shown.
[0073] The particle size and aspect ratio of the alumina products of Examples 1 to 3 and Comparative Example 1 were measured; and according to an alumina filling rate of 95.2%, the alumina products of Examples 1 to 3 and Comparative Example 1 were mixed with 500 viscosity vinyl silicone oil, and the viscosity and thermal conductivity of the alumina products of Examples 1 to 3 and Comparative Example 1 were measured, and the measurement results are shown in Table 1. From the measurement results in Table 1, it can be seen that the alumina products prepared in Examples 1 to 3 have a small particle size, and the particle size D50 is in the range of 0.2 to 0.8 μm, and in the range of 0.3 to 0.5 μm; the aspect ratio is closer to 1 (in the range of 0.8 to 1.2:1), and is spherical; the viscosity (1 inverted second and 10 inverted seconds) of the alumina products prepared in Examples 1 to 3 are significantly lower than that of the alumina products prepared in Comparative Example 1, indicating that the preparation method of the present application without adding additives and using ion exchange resin for cleaning can effectively reduce the viscosity of the product and improve the thermal conductivity of the product. Viscosity is one of the key indicators for powder thermal conductivity application testing. It is an indicator of the powder state after the powder is compounded in the silicone oil system. The lower the viscosity, the better the fluidity.
[0074] Table 1 Particle size, aspect ratio, viscosity and thermal conductivity measurement results of alumina products of Examples 1 to 3 and Comparative Example 1
[0075] D10 / μm D50 / μm D90 / μm Aspect Ratio Viscosity (1 reciprocal second) / mpa·s Viscosity (10 reciprocal seconds) / mpa·s Thermal conductivity / W / (m·K) Example 1 0.2 0.39 0.85 0.8:1 1313960 224887 6.48 Example 2 0.2 0.42 1.02 0.9:1 1236750 233020 6.50 Example 3 0.19 0.37 0.96 1.2:1 1524880 280603 6.50 Comparative Example 1 0.18 0.43 0.97 1.6:1 1802080 295254 6.14
[0076] The impurity element contents of the alumina products of Examples 1 to 3 and Comparative Example 1 were measured, and the measurement results are shown in Table 2. From Table 2, it can be seen that the contents of each impurity element (Na, K, Fe, Ca, Si) in the alumina products obtained in Examples 1 to 3 are significantly less than the impurity element contents in the alumina product obtained in Comparative Example 1, indicating that the content of impurity elements and the generation of impurities in subsequent products can be effectively reduced by not adding additives and using ion exchange resins for cleaning.
[0077] Table 2 Element content measurement results of alumina products of Examples 1 to 3 and Comparative Example 1
[0078] Na (ppm) K (ppm) Fe (ppm) Ca (ppm) Si (ppm) Total (ppm) Example 1 50 30 15 20 60 175 Example 2 60 35 20 23 57 195 Example 3 57 33 23 19 58 190 Comparative Example 1 100 50 48 103 94 395
[0079] The aluminum oxide product obtained in Example 1 was subjected to X-ray diffraction testing. The results are as follows: Figure 4 As shown, from Figure 4It can be seen that 2θ has diffraction peaks at 25.58, 35.15, 37.78, 43.36, and 57.50, which are characteristic peaks of α-alumina. The diffraction peaks are sharp and aligned, indicating that the alumina product is a nearly pure α-phase alumina product.
Claims
1. A method for preparing a small-size spherical alumina product, characterized in that: The following steps are involved: S1, placing aluminum-containing raw materials with a particle size of 0.1-1 μm in a kiln for calcination at a temperature of 1000-1200°C and a calcination holding time of 5-10 hours; S2, washing, drying, crushing and classifying the calcined product of step S1 to obtain a small-size spherical alumina product.
2. The method for preparing a small-size spherical alumina product according to claim 1, characterized in that: In step S1, the aluminum-containing raw material is one or more of industrial alumina, industrial aluminum hydroxide, and boehmite.
3. The method for preparing a small-size quasi-spherical alumina product according to claim 1 or 2, characterized in that: The particle size of the aluminum-containing raw material is 0.1-0.8 μm, or the particle size of the aluminum-containing raw material is 0.1-0.5 μm.
4. The method for preparing a small-size spherical alumina product according to claim 3, characterized in that: In step S1, the calcination temperature is 1050-1100°C, and the calcination holding time is 5-6 hours.
5. The method for preparing a small-size quasi-spherical alumina product according to claim 1, characterized in that: In step S2, cleaning and drying are performed, which specifically includes: Add the calcined product into a reaction kettle or a stirring tank, and stir and mix thoroughly with preheated pure water; Then, ion exchange resin is added to carry out a hydrothermal stirring reaction; After the hydrothermal stirring reaction, the ion exchange resin is removed, and the slurry is filtered or suction filtered and dried.
6. The method for preparing a small-size quasi-spherical alumina product according to claim 5, characterized in that: Also includes one or more of the following conditions: The pure water is pure water with a conductivity of less than 5 μs / cm; The calcined product is stirred and mixed with preheated pure water, and the pH is adjusted to 6.5-7.5; The amount of pure water added is 1.5 to 2 times the mass of the aluminum-containing raw material; The temperature of the hydrothermal stirring reaction is 50-80°C, and the reaction time is 2-3h; The ion exchange resin is one or more of benzenesulfonic acid, ammonium benzenesulfonate, and methyl lactate; The added amount of the ion exchange resin is 0.1-0.2% of the mass of the aluminum-containing raw material.
7. The method for preparing a small-size quasi-spherical alumina product according to claim 5 or 6, characterized in that: After the ion exchange resin is loaded into a filter bag or a porous container, it is put into a reaction kettle or a stirring tank to undergo a hydrothermal stirring reaction with the calcined product. After the hydrothermal stirring reaction, the filter bag or porous container loaded with the ion exchange resin is taken out to obtain the slurry.
8. The method for preparing a small-size quasi-spherical alumina product according to any one of claims 1, 5 or 6, characterized in that: In step S1, the kiln is one of a push plate kiln, a tunnel kiln, and a shuttle kiln; And / or, in step S2, the dried product is crushed by a ball mill and / or a jet mill, and the crushing time is 5 to 6 hours.
9. A small-particle spherical alumina product, characterized in that: The small-particle quasi-spherical alumina product has a particle size of 0.1-10 μm, an aspect ratio of 0.8-1.4:1, an α-phase content of more than 95%, and a total impurity element content of less than 200 ppm.
10. The small-size quasi-spherical alumina product according to claim 9, characterized in that: The small-particle-size spherical alumina product has a particle size of 0.2-0.8 μm.